Immune Responses to Circulating and Vaccine Viral Strains in HIV-Infected and Uninfected Children and Youth Who Received the 2013/2014 Quadrivalent Live-Attenuated Influenza Vaccine - Weinberg, Adriana; Curtis, Donna; Ning, Mariangeli Freitas; Claypool, David Jeremy; Jalbert, Emilie; Patterson, Julie; Frank, Daniel N.; Ir, Diana; Armon, Carl (Frontiers in Immunology, 2016)
The live attenuated influenza vaccine (LAIV) has generally been more efficacious than the inactivated vaccine in children. However, LAIV is not recommended for HIV-infected children because of insufficient data. We compared cellular, humoral and mucosal immune responses to the 2013-2014 LAIV quadrivalent (LAIV4) in HIV-infected and uninfected children 2 to 25 years of age (yoa). We analyzed the responses to the vaccine H1N1 (H1N1-09), to the circulating H1N1 (H1N1-14), which had significant mutations compared to H1N1-09 and to B Yamagata (BY), which had the highest effectiveness in 2013-2014. Forty-six HIV-infected and 56 uninfected participants with prior influenza immunization had blood and nasal swabs collected before and after LAIV4 for IFN T and IgG/IgA memory B cell responses (ELISPOT), plasma antibodies [hemagglutination inhibition (HAI) and microneutralization (MN)], and mucosal IgA (ELISA). The HIV-infected participants had median CD4+ T cells=645 cells/µL and plasma HIV RNA=20 copies/mL. Eighty-four% were on cART. Regardless of HIV status, significant increases in T cell responses were observed against BY, but not against H1N1-09. H1N1-09 T cell immunity was higher than H1N1-14 both before and after vaccination. LAIV4 significantly increased memory IgG B cell immunity against H1N1-14 and BY in uninfected, but not in HIV-infected participants. Regardless of HIV status, H1N1-09 memory IgG B cell immunity was higher than H1N1-14 and lower than BY. There were significant HAI titer increases after vaccination in all groups and against all viruses. However, H1N1-14 MN titers were significantly lower than H1N1-09 before and after vaccination overall and in HIV-uninfected vaccinees. Regardless of HIV status, LAIV4 increased nasal IgA concentrations against all viruses. The fold-increase in H1N1-09 IgA was lower than BY. Overall, participants <9 yoa had decreased BY-specific HAI and nasal IgA responses to LAIV4. In conclusion, HIV-infected and uninfected children and youth had comparable responses to LAIV4. H1N1-09 immune responses were lower than BY and higher than H1N1-14, suggesting that both antigenic mismatches between circulating and vaccine H1N1 and lower immunogenicity of the H1N1 vaccine strain may have contributed to the decreased H1N1 effectiveness of 2013-2014 LAIV4.